The Use of Digital for Public Service Provision in Sub-Saharan Africa - Jenny C. Aker; Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2020)
Accessible, affordable and qualitative public service delivery is critical for the well-being of populations living in developing countries and for the functioning of their economy, but these services are often undermined by market imperfections and weak institutions (Aker, 2017). In light of these challenges, the digitalization process observed in many low and middle-income countries, resulting from the sustained growth in the coverage of mobile networks and the concomitant reduction in information and communication technologies (ICTs) usage gap opened up economic opportunities and helped leapfrog a number of development obstacles, especially in remote rural areas (Aker and Mbiti, 2010; Aker 2011; Aker 2017). ICTs, more particularly broadband Internet and mobile technologies have the potential to become general-purpose technologies (Bresnahan & Trajtenberg, 1995) called upon to play an increasing role in the development process in Sub-Saharan Africa (SSA), including West Africa. [...]
Keywords: 330